2022
DOI: 10.1097/tld.0000000000000270
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Communication Effectiveness in Adults Who Stutter

Abstract: The purpose of this study was to examine the benefits of a treatment approach for adults who stutter that focuses on core communication competencies rather than attempt to modify speech fluency. Eleven adults who stutter completed a 12-week treatment program at The Arthur M. Blank Center for Stuttering Education and Research. Pre- and posttreatment measures included (a) self-reported cognitive and affective aspects of stuttering (Overall Assessment of the Speaker's Experience of Stuttering [OASES], Self-Percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 65 publications
(105 reference statements)
1
25
0
Order By: Relevance
“…Coalson et al [11] examined self-reported clinical outcomes from 33 adults who stutter after an 11-week communication-centered treatment (for greater detail see Byrd et al [10]) program similar to the one-week treatment program for children described in Byrd et al [9,[26][27]).…”
Section: Preliminary Findings With Adults Who Stuttermentioning
confidence: 99%
See 2 more Smart Citations
“…Coalson et al [11] examined self-reported clinical outcomes from 33 adults who stutter after an 11-week communication-centered treatment (for greater detail see Byrd et al [10]) program similar to the one-week treatment program for children described in Byrd et al [9,[26][27]).…”
Section: Preliminary Findings With Adults Who Stuttermentioning
confidence: 99%
“…These data challenge the assumption that fluency must be targeted to facilitate positive perspectives of self and/or communication in persons who stutter. In fact, Byrd and colleagues [9][10][11][26][27] provide evidence that significant positive changes in communication attitudes, and communication competence, can be reliably attained through participation in a treatment that focuses on improving overall communication and explicitly excludes clinical goals that attempt to hide, eliminate, or modify stuttered speech in children and adults following CCT. Byrd et al [26, n = 23, ages 7-to 14-years old] examined changes in cognitive and affective wellbeing before and after treatment reported by 23 children and adolescents who stutter and their parents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Then, Tichenor et al (2022) highlight the importance of understanding the experience of people who stutter. Finally, Byrd et al (2022) share preliminary results from their communication effectiveness intervention for adults who stutter. In summary, Hampton Wray (2022) and the authors of this issue provide an excellent overview of critical aspects of stuttering, calling for clinicians and researchers to focus their attention beyond disfluencies.…”
mentioning
confidence: 99%
“…In the final article in this issue, Byrd et al (2022) evaluated a treatment approach for adults who stutter that focuses on communication competencies without any goals or evaluation of speech fluency or stuttered events. The treatment program focuses on both affective and cognitive aspects of stuttering (outlined in Tichenor et al, 2022) by targeting speaking confidently, communicating effectively, and advocating meaningfully with the aim of improving quality of life.…”
mentioning
confidence: 99%